Method for manufacturing surface-modified electrode active material, and electrode and lithium secondary battery manufactured thereby.

JP2026530372APending Publication Date: 2026-09-08LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026509291
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-09-02
Publication Date
2026-09-08

AI Technical Summary

Benefits of technology

【0073】 本発明の実施形態による表面改質電極活物質の製造方法は、酸化物系固体電解質を溶媒に予備分散させて、電極活物質の表面上に酸化物系固体電解質を均等に分布することができる。このため、前記酸化物系固体電解質粒子では、前記電極活物質と電解質との接触界面において、電解質中のリチウムイオンの脱溶媒和過程に伴う活性化エネルギーが低減され、脱溶媒和を迅速化することができる。また、これにより、前記電極活物質粒子の周囲でリチウムイオン伝導性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026530372000001_ABST
    Figure 2026530372000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing a surface-modified electrode active material that can improve output characteristics and low-temperature characteristics, and to an electrode and lithium secondary battery produced thereby. The method for producing the surface-modified electrode active material includes the steps of: producing a solid electrolyte dispersion containing an oxide-based solid electrolyte and a solvent; coating the surface of an electrode active material with the solid electrolyte dispersion; and heat-treating the coated electrode active material to form a surface-modified electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Cross-Reference to Related Applications This application claims the benefit of priority based on Korean Patent Application No. 10-2023-0118577 filed on September 6, 2023, and all contents disclosed in the document of said Korean patent application are incorporated as part of the present specification.

[0002] The present invention relates to a method for producing a surface-modified electrode active material capable of improving the output characteristics and low-temperature characteristics of a lithium secondary battery, and an electrode and a lithium secondary battery produced thereby. Background Art

[0003] In recent years, as the application fields of lithium secondary batteries have rapidly expanded not only to power supply for electronic devices such as electricity, electronics, communications, and computers, but also to power storage and supply for large-area devices such as automobiles and power storage devices, demands for lithium secondary batteries with high capacity, high output, long life, and high stability have been increasing.

[0004] Lithium secondary batteries are generally configured to include a positive electrode, a negative electrode, a separation membrane, and an electrolyte containing a lithium salt and an organic solvent, and transfer of lithium ions through the electrolyte occurs during charge and discharge processes.

[0005] Lithium ions in the electrolyte are surrounded by organic solvents and exist in a solvated state. Therefore, in order for such lithium ions in the electrolyte to move and be inserted into the electrode active material, they need to undergo a desolvation process in which the lithium ions separate or desorb from the organic solvent molecules. Accordingly, smooth progress of such a desolvation process can affect the output, resistance, stability and the like of the lithium secondary battery.

[0006] On the other hand, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2, LiMn2O4, etc.), and lithium iron phosphate compounds (LiFePO4) are used as positive electrode active materials for lithium secondary batteries. In particular, NCM-based lithium composite transition metal oxides were developed to improve the low thermal stability while maintaining the excellent reversible capacity of LiNiO2. However, conventional NCM-based lithium composite transition metal oxides have insufficient capacity characteristics and have limited applicability.

[0007] To address these issues, recent research has focused on increasing the Ni content in NCM-based lithium composite transition metal oxides. However, in the case of high-concentration nickel cathode active materials, while the capacity increases, the Ni content increases depending on the depth of charge. 2+ From Ni 3+ / 4+ A problem arises when oxidation causes rapid oxygen desorption, and the desorbed oxygen reacts with the electrolyte, altering the material's inherent properties, leading to lattice structure instability and ultimately structural collapse.

[0008] Therefore, there is a continuing need for the development of technologies that can accelerate the desolvation of lithium ions in the electrolyte, thereby improving the output characteristics of lithium secondary batteries while maintaining excellent low-temperature characteristics. [Overview of the project] [Problems that the invention aims to solve]

[0009] Therefore, the present invention provides a method for producing a surface-modified electrode active material that can accelerate the desolvation of lithium ions in the electrolyte, thereby improving the output characteristics of lithium secondary batteries while maintaining excellent low-temperature characteristics such as high output at low temperatures.

[0010] The present invention also provides electrodes and lithium secondary batteries that are manufactured thereby and exhibit improved power characteristics and low-temperature characteristics. [Means for solving the problem]

[0011] The following describes a method for producing surface-modified electrode active material according to specific embodiments of the invention.

[0012] The terms and words used in this specification and in the claims should not be interpreted in a manner limited to their ordinary or dictionary meanings, but rather in a manner and concept consistent with the technical idea of ​​the present invention, in accordance with the principle that inventors may appropriately define the concepts of terms in order to best describe their invention.

[0013] The terms used herein are for illustrative purposes only and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise.

[0014] In this specification, terms such as “includes,” “equip,” or “have” indicate the presence of implemented features, figures, stages, components, or combinations thereof, and it should be understood that the possibility of the presence or addition of one or more other features, figures, stages, components, or combinations thereof is not excluded in advance.

[0015] Method for producing surface-modified electrode active material According to one embodiment of the present invention, a method for producing a surface-modified electrode active material is provided, comprising the steps of: producing a solid electrolyte dispersion containing an oxide-based solid electrolyte and a solvent; coating the surface of an electrode active material with the solid electrolyte dispersion; and heat-treating the coated electrode active material to form a surface-modified electrode active material.

[0016] In particular, as shown in Figure 1, the method for producing the surface-modified electrode active material allows for the even distribution of the oxide-based solid electrolyte on the surface of the electrode active material by pre-dispersing the oxide-based solid electrolyte in a solvent. This distinguishes it from conventional surface-modified active materials where the oxide-based solid electrolyte particles aggregate and cannot be evenly dispersed. As a result, the oxide-based solid electrolyte particles reduce the activation energy associated with the desolvation process of lithium ions in the electrolyte at the interface where the electrode active material and the electrolyte come into contact, thereby accelerating desolvation. Furthermore, this improves lithium ion conductivity around the electrode active material particles.

[0017] First, an oxide-based solid electrolyte can be uniformly dispersed in a solvent to produce a solid electrolyte dispersion containing the oxide-based solid electrolyte and the solvent. This allows for pre-dispersion of the oxide-based solid electrolyte in the solvent, enabling even distribution of the oxide-based solid electrolyte on the surface of the electrode active material during the coating stage described later.

[0018] In an exemplary embodiment, the dispersion preparation step may include mixing 5 to 70 parts by weight of an oxide-based solid electrolyte and 30 to 95 parts by weight of a solvent. When the oxide-based solid electrolyte and solvent are mixed within this range, if the oxide-based solid electrolyte is 70 parts by weight or more, it becomes difficult to control the D50 value to 100 nm to 1 μm, and if the solid electrolyte is 5 parts by weight or less, the dispersion energy efficiency transferred to the particle surface becomes low, and the dispersion time may become longer.

[0019] In an exemplary embodiment, the dispersion preparation step may involve using one or more methods, such as sonication, a high-shear mixer, a high-pressure homogenizer, and bead milling, to disperse the oxide-based solid electrolyte.

[0020] In particular, to improve the dispersion efficiency of high-concentration oxide-based solid electrolyte dispersions with nanoparticle size and minimize oxidation of the oxide-based solid electrolyte due to heat generated during the dispersion process, the dispersion can be dispersed using a bead milling method with a maximum dispersion temperature of 40°C or less and a dispersion time of 3 hours or less.

[0021] In an exemplary embodiment, the oxide-based solid electrolyte in the solid electrolyte dispersion may have one or more particle size distributions where D50 is 100 nm to 1 μm and D90 is 400 nm to 1.5 μm. For example, it may have one or more particle size distributions where D50 is 300 to 700 nm, D90 is 400 to 900 nm, and span is 1 or less. When oxide-based solid electrolyte particles are uniformly distributed within the above range, excellent power characteristics and low-temperature characteristics can be obtained.

[0022] In exemplary embodiments, any solid electrolyte containing lithium in its structure and having a lithium ion source, and having the form of a lithium metal oxide or lithium metal phosphorus oxide, can be used as the oxide-based solid electrolyte.

[0023] For example, one or more lithium metal oxides or lithium metal phosphoroxides selected from Nasicon-type solid electrolytes, Lisicon-type solid electrolytes, Garnet-type solid electrolytes, Perovskite-type solid electrolytes, and LiPON-type solid electrolytes are mentioned. More specifically, one or more compounds selected from the group consisting of LAGP (lithium aluminum germanium phosphate) compounds, LLZO (lithium lanthanum zirconium oxide) compounds, LATP (lithium aluminum titanium phosphate) compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) compounds, LLTO (lithium lanthanum titanium oxide) compounds, LSTP (lithium silicon titanium phosphate) compounds, and LGPO (lithium germanium phosphate) compounds are mentioned.

[0024] Among others, NASICON-type solid electrolytes such as the aforementioned LAGP-based compounds or LATP-based compounds can be suitably used from the aspect of accelerating the desolvation of lithium ions at the interface between the active material layer and the electrolyte, and improving the ionic conductivity and output of a lithium secondary battery.

[0025] Next, the solid electrolyte dispersion can be coated on the surface of the electrode active material. Specifically, the solid electrolyte dispersion can be mixed with a positive electrode active material to form a uniform coating layer such that nanoparticles of the oxide-based solid electrolyte dispersion are uniformly distributed on the surface of the positive electrode active material.

[0026] In an exemplary embodiment, the step of coating with the solid electrolyte dispersion may be performed by one or more methods selected from spray coating, high-speed homogeneous mixing, and fluidized bed coating methods.

[0027] In an exemplary embodiment, the positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically may include a lithium metal oxide containing lithium and one or more metals such as iron, cobalt, manganese, nickel or aluminum.

[0028] Specifically, the lithium metal oxide includes lithium-manganese based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt based oxides (e.g., LiCoO2, etc.), lithium-nickel based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese based oxides (e.g., LiNi 1-Y Mn Y O2 (wherein 0<Y<1), LiMn 2-Z Ni Z O4 (wherein 0<Z<2), etc.), lithium-nickel-cobalt based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (wherein 0<Y1<1), etc.), lithium-manganese-cobalt based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (wherein 0<Y2<1), LiMn2-Z1 Co Z1 Z1O4 (where 0<Z1<2), etc.), lithium-nickel-manganese-cobalt-based oxides (for example, Li(Ni p Co q Mn r )O2 (where 0<p<1, 0<q<1, 0<r<1, p+q+r=1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0<p1<2, 0<q1<2, 0<r1<2, p1+q1+r1=2), etc.), lithium-nickel-cobalt-transition metal (M) oxides (for example, Li(Ni p2 Co q2 Mn r2 M s2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo, and p2, q2, r2 and s2 are each independent atomic fractions of elements, satisfying 0<p2<1, 0<q2<1, 0<r2<1, 0<s2<1, p2+q2+r2+s2=1), etc., or lithium iron phosphate oxides (for example, Li 1+a Fe 1-x M x (PO 4-b )X b (where M is one or more selected from Al, Mg and Ti, X is one or more selected from F, S and N, -0.5≦a≦+0.5, 0≦x≦0.5, 0≦b≦0.1). Any one or more of these compounds may be included.

[0029] Among them, the positive electrode active material includes a lithium metal oxide containing lithium and two or more metals selected from the group consisting of nickel, manganese, cobalt and aluminum, and the lithium metal oxide may contain 60 mol% or more, alternatively 60 to 99 mol%, alternatively 70 to 95 mol% of nickel relative to the total metal content excluding lithium. Such a lithium metal oxide may be, for example, represented by the following Chemical Formula 1: [Chemical Formula 1] Li x Ni a Cob M 1 c M 2 d O2 In the above chemical formula 1, M 1 M may be one or more selected from Mn and Al, or a combination thereof. 2 a may be one or more elements selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, and may be 0.90≦x≦1.1, or 0.95≦x≦1.08, or 1.0≦x≦1.08, or 0.60≦a<1.0, or 0.70≦a≦0.99, or 0.80≦a≦0.95.

[0030] On the other hand, the positive electrode active material may have an average particle size (D50) of 4 to 15 μm, 7 to 13 μm, or 8 to 12 μm.

[0031] By using a lithium metal oxide containing such a high nickel content as the positive electrode active material and combining it with an oxide-based solid electrolyte, the output and capacity characteristics of lithium secondary batteries can be further improved.

[0032] In exemplary embodiments, the oxide-based solid electrolyte may be present in an amount of 0.3 to 5 parts by weight per 100 parts by weight of the electrode active material, in order to accelerate the desolvation of lithium ions at the interface between the active material layer and the electrolyte and improve lithium ion conductivity without hindering the insertion and desolvation processes of lithium ions by the positive electrode active material.

[0033] Next, the coated electrode active material can be heat-treated to form a surface-modified electrode active material.

[0034] In exemplary embodiments, it is preferable to heat-treat the oxide-based solid electrolyte at a temperature above the glass transition temperature (Tg), and after heat treatment, a uniform coating thin film layer is fired to form oxide-based solid electrolyte nanoparticles uniformly coated on the surface of the active material, thereby forming a modified electrode active material.

[0035] In an exemplary embodiment, the heat treatment step may involve firing at a temperature of 600 to 1000°C for 1 to 3 hours to form the surface-modified electrode active material.

[0036] On the other hand, it is possible to remove the solvent prior to the firing process. Specifically, the electrode active material coated with the oxide-based solid electrolyte can be pre-dried at 130°C for 2 hours to remove the NMP solvent. The dried oxide-based solid electrolyte coated active material can then be subjected to a firing process at 800°C for 2 hours to form a surface-modified electrode active material.

[0037] Electrodes for lithium secondary batteries and lithium secondary batteries According to another embodiment of the present invention, an electrode for a lithium secondary battery is provided, comprising a metal current collector; and an active material layer formed on the metal current collector, the active material being the surface-modified electrode active material produced by the method for producing the surface-modified electrode active material described above.

[0038] The following describes in more detail an electrode for a lithium secondary battery and a lithium secondary battery containing the same according to one embodiment. However, although the following description will focus on an embodiment in which the electrode for the lithium secondary battery is the positive electrode, the scope of the invention is not limited thereto, and the electrode of the above embodiment may also be the negative electrode.

[0039] The positive electrode for a lithium secondary battery according to the above embodiment includes a metal current collector. Such a metal current collector is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with a surface treatment of carbon, nickel, titanium, silver, etc. can be used.

[0040] Furthermore, the active material layer on the metal current collector may further contain an oxide-based solid electrolyte having a conductive material and a lithium ion source, in addition to the surface-modified electrode active material, and may selectively further contain a binder.

[0041] On the other hand, the conductive material contained in the active material layer is a component for further improving the conductivity of the positive electrode active material, and such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. For example, carbon powder such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystalline structure; conductive nanomaterials such as carbon nanofibers or carbon nanotubes; fluorinated carbon powder; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives can be used. In particular, by including conductive nanomaterials such as carbon nanotubes or carbon nanofibers in the conductive material, the resistance of the lithium secondary battery containing the positive electrode of one embodiment can be further reduced and the output characteristics can be further improved.

[0042] Typically, the conductive material may be present in an amount of 1 to 20% by weight, 1 to 15% by weight, or 1 to 10% by weight, based on the total weight of the active material layer.

[0043] The binder selectively included in the active material layer is a component that promotes bonding between the positive electrode active material and conductive materials, and to the current collector. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, nitrile rubber, styrene-butadiene rubber, or fluororubber, and a mixture or copolymer of two or more selected from these may be used.

[0044] Typically, the binder may be present in an amount of 1 to 20% by weight, 1 to 15% by weight, or 1 to 10% by weight, based on the total weight of the positive electrode active material layer.

[0045] Furthermore, a filler may be selectively added to the positive electrode as a component to suppress its expansion. Such a filler is not particularly limited as long as it can suppress the expansion of the electrode without inducing a chemical change in the battery, and for example, olefin polymers such as polyethylene and polypropylene; fibrous materials such as glass fibers and carbon fibers; etc. can be used.

[0046] The positive electrode of the above-described embodiment can be manufactured, for example, by dispersing and mixing the positive electrode active material, oxide-based solid electrolyte, binder, and conductive material in a dispersion medium (solvent) to form a slurry, coating this slurry onto a metal current collector, and then drying and rolling it. In this case, the dispersion medium can be NMP (N-methyl-2-pyrrolidone), DMF (Dimethyl formamide), DMSO (Dimethyl sulfoxide), ethanol, isopropanol, water, and mixtures thereof, but is not necessarily limited to these.

[0047] Furthermore, a lithium secondary battery is provided that includes a positive electrode; a negative electrode; and an electrolyte comprising a lithium salt and a non-aqueous organic solvent, wherein the aforementioned lithium secondary battery electrode is used as the positive electrode. Lithium secondary batteries of such other embodiments can exhibit low-temperature characteristics along with excellent power characteristics.

[0048] In lithium secondary batteries of such other embodiments, the negative electrode may have a conventional configuration known in the art. For example, the negative electrode may include a negative electrode current collector and a negative electrode active material layer formed on such a negative electrode current collector, the negative electrode active material layer of which may include, for example, a negative electrode active material and, optionally, additives such as conductive materials, binders, and fillers. Furthermore, such a negative electrode can be formed by a common method of dispersing and mixing the components of the negative electrode active material layer in a dispersion medium (solvent) to form a slurry, coating this slurry onto the negative electrode current collector, and then drying and rolling it.

[0049] In this case, the negative electrode current collector can be made of platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), copper (Cu), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (In doped SnO2), FTO (F doped SnO2), and alloys thereof, as well as copper (Cu) or stainless steel with a surface treatment of carbon (C), nickel (Ni), titanium (Ti), or silver (Ag), but is not necessarily limited to these. The negative electrode current collector may take the form of foil, film, sheet, punched material, porous material, foam, etc.

[0050] Furthermore, the negative electrode active material can be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds that can alloy with lithium, such as Si, Al, Sn, Pb, Sb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metallic oxides that can be doped and dedoped with lithium, such as SiOβ (0<β<2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites. One or more of these mixtures can be used. A metallic lithium thin film may also be used as the negative electrode active material.

[0051] In addition, all types of carbonaceous materials can be used, including low-crystalline carbon and high-crystalline carbon. Typical low-crystalline carbons include soft carbon and hard carbon, while typical high-crystalline carbons include amorphous, plate-like, flaky, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes.

[0052] The negative electrode active material described above may be present in an amount of 60-99% by weight, 70-99% by weight, or 80-98% by weight, based on the total weight of the negative electrode active material layer.

[0053] In other embodiments, the negative electrode may not include a negative electrode active material layer, but may include only a negative electrode current collector. In such a negative electrode, lithium ions that have moved from the positive electrode during the charge-discharge process are electrodeposited onto the negative electrode current collector, forming a lithium metal layer, which can then be used as the negative electrode active material.

[0054] On the other hand, the binder and conductive material included in the negative electrode active material layer can be the same as those described earlier for the positive electrode, so no further explanation regarding this is necessary. Additionally, when the electrode for the lithium secondary battery of the embodiment described above becomes the negative electrode, the negative electrode active material layer may further include an oxide-based solid electrolyte having the lithium ion supply source described above, in which case the oxide-based solid electrolyte can satisfy the D50 ratio described above with respect to the negative electrode active material particles.

[0055] The lithium secondary batteries of the other embodiments described above include an electrolyte comprising a lithium salt and a non-aqueous organic solvent. Such an electrolyte acts as a transfer medium for lithium ions between the positive and negative electrodes, and such lithium ions exist in the electrolyte in a solvated state, while being able to be inserted into the electrode active material via desolvation at the interface between the electrolyte and the electrodes. As described above, in the secondary batteries of the other embodiments, such desolvation is accelerated, which can result in improved output characteristics and other features.

[0056] The lithium salt contained in the electrolyte is used as a medium for transferring ions in a lithium secondary battery. The lithium salt is, for example, Li as a cation. + Includes F - Cl - , Br - , I - NO3 - , N(CN)2 - BF4 - ClO4 - B 10 Cl 10 - AlCl4 - AlO2 - PF6- CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - BF2C2O4 - BC4O8 - PF4C2O4 - PF2C4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - , C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - (CF3SO2) 2CH - CF3(CF2)7SO3 - and SCN - It can also contain anions selected from the group consisting of the following.

[0057] Specifically, the lithium salts are LiCl, LiBr, LiI, LiBF4, LiClO4, and LiB 10 Cl 10 It may contain one or more selected from the group consisting of LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (Lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2).

[0058] The concentration of the lithium salt can be appropriately changed within a range that is normally usable, and may be included in the electrolyte at a concentration of 0.5 M to 6 M, or 1 M to 5 M.

[0059] In a more specific embodiment, the electrolyte may contain lithium salt at a relatively low concentration of 0.5 M to less than 2 M, or 0.7 M to 1.5 M. In this case as well, the lithium secondary battery of the other embodiment can exhibit improved output characteristics due to the rapid desolvation of lithium ions by the action of the electrode in the above-described embodiment. As a result, problems such as increased viscosity of the electrolyte, decreased fluidity, poor ionic conductivity of the electrolyte at low temperatures, and decreased battery output caused by the application of electrolyte compositions containing high concentrations of lithium salt are resolved, and excellent low-temperature characteristics of the lithium secondary battery can be achieved.

[0060] On the other hand, in other embodiments of the invention, the electrolyte may contain a lithium salt at a high concentration of 2M to 6M, or 2.5M to 5.5M. In this case, the inclusion of a high concentration of lithium salt and the application of the electrode of one embodiment further accelerate the desolvation of lithium ions, thereby further improving the output characteristics of the secondary battery.

[0061] Furthermore, by applying the electrode of the above embodiment, lithium ion conductivity can be improved and resistance reduced even at low temperatures. This reduces the deterioration of low-temperature output characteristics caused by high-concentration lithium salts, etc.

[0062] On the other hand, the type of non-aqueous organic solvent included in the electrolyte is not particularly limited, and any organic solvent that has been known to be applicable to lithium-ion battery electrolytes can be used. Examples of such organic solvents include one or more selected from the group consisting of carbonate-based solvents, ether-based solvents, nitrile-based solvents, phosphate-based solvents, and sulfone-based solvents.

[0063] More specifically, as the carbonate-based solvent, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, methyl propyl carbonate, ethyl methyl carbonate, ethyl propyl carbonate, or methyl (2,2,2-trifluoroethyl) carbonate can be used, and as the phosphate-based solvent, trimethyl phosphate, triethyl phosphate, or 2-(2,2,2-trifluoroethoxy)-1,3,2-dioxaphosphorane 2-oxide can be used.

[0064] Furthermore, as the ether-based solvent, dibutyl ether, tetraglyceride, diglyceride, dimethoxyethane, or tetrahydrofuran derivatives such as 2-methyltetrahydrofuran can be used, and as the nitrile-based solvent, succinonitrile, adiponitrile, sebaconitrile, acetonitrile, or propionitrile can be used. In addition, as the sulfone-based solvent, dimethyl sulfone, ethyl methyl sulfone, or sulforane can be used.

[0065] On the other hand, the electrolyte may further include, in addition to the lithium salt and non-aqueous organic solvent described above, a diluent that exhibits solubility in the lithium salt that is 10 times or more less than that of the non-aqueous organic solvent. Such a diluent is an organic solvent that is miscible with the non-aqueous organic solvent and exhibits substantially no solubility in the lithium salt, and may be, for example, an ether-based solvent having a fluorine-substituted alkyl group, and more specifically, may include one or more selected from the group consisting of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE), methoxynononafluorobutane (MOFB), and ethoxynononafluorobutane (EOFB).

[0066] When such a diluent is further included, a locally high concentration of lithium salt may be present in the non-aqueous organic solvent within the electrolyte, and the lithium salt may not be substantially present in the diluent. In this way, the presence of a locally high concentration of lithium salt in the electrolyte in a solvated form further improves the output characteristics of the lithium secondary battery while reducing the increase in viscosity and decrease in fluidity of the electrolyte. In addition, when the electrode of one embodiment is applied together with such a locally high-concentration salt electrolyte, it is possible to improve lithium ion conductivity and reduce resistance even at low temperatures, thereby reducing the decrease in low-temperature output characteristics caused by high-concentration lithium salts, etc.

[0067] The amount of the diluent used can be adjusted according to the type of non-aqueous organic solvent and lithium salt, as well as the overall concentration of the lithium salt. For example, the diluent may be included in the electrolyte in a quantity such that the molar ratio of the diluent to the non-aqueous organic solvent is 1:0.2 to 1:5, or 1:0.5 to 1:2.

[0068] On the other hand, the lithium secondary battery of the other embodiment described above may further include a porous separator membrane interposed between the positive electrode and the negative electrode.

[0069] Such porous separation membranes can be made from polyethylene, olefin polymers such as polypropylene, glass fibers, etc., in the form of sheets, multilayer membranes, fine porous films, woven fabrics, and nonwoven fabrics, but are not necessarily limited to these forms. However, it is preferable to use porous polyethylene or porous glass fiber nonwoven fabric (glass filter) as the separation membrane, and it is even more preferable to use porous polyethylene as the separation membrane. The separation membrane may be a thin insulating film with high ion permeability and mechanical strength, and the pore size of the separation membrane may generally be in the range of 0.01 to 10 μm, and the thickness may generally be in the range of 5 to 300 μm, but is not limited to these.

[0070] Furthermore, in other examples of the lithium secondary battery, the separation membrane may not be present, and the electrolyte described above may be interposed between the positive and negative electrodes in the form of an electrolyte membrane or electrolyte film. In this case, the electrolyte membrane or electrolyte film may be in the form of a polymer matrix containing the aforementioned lithium salt and non-aqueous organic solvent, and a well-known polymer-based solid electrolyte can be used as the polymer matrix. In this case, the lithium secondary battery of the other embodiment may be a semi-solid battery that uses both a liquid electrolyte and a solid electrolyte.

[0071] On the other hand, lithium secondary batteries of the other embodiments described above can be manufactured by conventional methods of the art. For example, an electrode assembly including a positive electrode, a negative electrode, and a separator membrane (or electrolyte membrane) may be housed in a case and manufactured by injecting and impregnating the electrolyte described above.

[0072] Such lithium secondary batteries are suitable not only for use as battery cells in power supplies for small devices, but also particularly suitable for use as unit batteries in battery modules that power medium to large devices. [Effects of the Invention]

[0073] The method for producing a surface-modified electrode active material according to an embodiment of the present invention allows for the uniform distribution of an oxide-based solid electrolyte on the surface of the electrode active material by pre-dispersing the oxide-based solid electrolyte in a solvent. Therefore, in the oxide-based solid electrolyte particles, the activation energy associated with the desolvation process of lithium ions in the electrolyte is reduced at the contact interface between the electrode active material and the electrolyte, thereby accelerating desolvation. Furthermore, this improves lithium ion conductivity around the electrode active material particles.

[0074] Furthermore, since the output characteristics of lithium secondary batteries can be improved without applying new electrolyte compositions containing high-concentration lithium salts, problems such as increased viscosity and decreased fluidity of the electrolyte, as well as decreased ionic conductivity and battery output at low temperatures, that occur when applying the aforementioned new electrolyte compositions are resolved, and excellent low-temperature characteristics of lithium secondary batteries can be achieved.

[0075] In addition, when applied to an electrolyte composition containing the aforementioned high-concentration lithium salt, the application of the electrode of the present invention facilitates the desolvation of lithium ions, improves lithium ion conductivity, and reduces resistance. Therefore, it is possible to further improve the output characteristics of lithium secondary batteries with high-concentration lithium salts while reducing the deterioration of low-temperature characteristics.

[0076] Therefore, the present invention can greatly contribute to the development of next-generation lithium secondary batteries that exhibit improved output characteristics and low-temperature characteristics. [Brief explanation of the drawing]

[0077] [Figure 1] This paper compares the manufacturing method according to the present invention, in which oxide-based solid electrolytes are pre-dispersed in a solvent and uniformly distributed on the surface of an electrode active material, with the conventional surface-modified active material, where oxide-based solid electrolyte particles aggregate with each other and cannot be uniformly dispersed. [Figure 2] The SEM and EDS mapping images of the Ti element of the positive electrode active material according to Comparative Example 1 and Example 1 of the present invention are shown. [Figure 3] The results of the evaluation of the electrochemical properties of lithium secondary batteries manufactured using the positive electrodes of Example 2, Example 3, and Comparative Examples 2 and 3 of the present invention are shown. [Figure 4] This graph compares the results of resistance measurements at different states of charge (SOC) for lithium secondary batteries manufactured using the positive electrodes of Example 2, Example 3, Comparative Example 2, and Comparative Example 3 of the present invention. [Modes for carrying out the invention]

[0078] The invention will be described in more detail below through specific examples. However, the following examples are merely illustrative for understanding the invention and do not limit the scope of the invention.

[0079] Example 1-1: Production of surface-modified cathode active material D50: Li 300nm 1.3 Al 0.3 Ti 1.7 A solid electrolyte dispersion was prepared by mixing 25 g of (PO4)3 oxide-based solid electrolyte (LATP) with 50 g of NMP, adding a bead mill to the mixture, and then dispersing it for 40 minutes using a spike mill.

[0080] As the positive electrode active material, lithium nickel cobalt manganese composite oxide (NCM603; D50: 5μm) containing 80 mol% nickel in the total transition metal was used. The prepared dispersion was added to 5 kg of the positive electrode active material, and then mixed and stirred at 3000 rpm for 30 minutes using a homogeneous mixer. After drying the NMP solvent at 130°C for 1 hour, the material was calcined at 800°C for 2 hours to produce a surface-modified positive electrode active material with a uniform solid electrolyte coating film.

[0081] Examples 1-2: Production of surface-modified cathode active material D50: Li 300nm 1.3 Al 0.3 Ti 1.7A solid electrolyte dispersion was prepared by mixing 50 g of (PO4)3 oxide-based solid electrolyte (LATP) and 50 g of NMP, then adding a bead mill to the mixture and performing a dispersion treatment for 40 minutes using a spike mill.

[0082] As the positive electrode active material, lithium nickel cobalt manganese composite oxide (NCM603; D50: 5μm) containing 65 mol% nickel in the total transition metal was used. The prepared dispersion was added to 5 kg of the positive electrode active material, and then mixed and stirred at 3000 rpm for 30 minutes using a homogeneous mixer. After drying the NMP solvent at 130°C for 1 hour, the material was calcined at 800°C for 2 hours to produce a surface-modified positive electrode active material with a uniform solid electrolyte coating film.

[0083] Example 2: Manufacturing of a lithium secondary battery Carbon nanotubes were used as the conductive material, and polyvinylidene fluoride (PVDF) was used as the binder. A cathode active material slurry was prepared by mixing 97 parts by weight of the surface-modified cathode active material from Example 1-1, 1.5 parts by weight of the conductive material, and 1.5 parts by weight of the binder. The prepared slurry was coated onto an aluminum current collector and dried to prepare the cathode. At this time, the particle size distribution of the oxide-based solid electrolyte (LATP) was measured using a laser diffraction particle size analyzer (Malvern's Mastersizer 3000), and the results were D10: 0.234 μm, D50: 0.345 μm, D90: 0.495 μm, and span: 0.757. Graphite was used as the anode active material, and without using an oxide-based solid electrolyte, the anode was prepared by mixing the anode active material, conductive material, and binder in a weight ratio of 96.5:1.5:2, and then performing the same process as for the cathode.

[0084] A lithium secondary battery in bicell form was manufactured by placing the prepared positive and negative electrodes facing each other, placing a 15 μm thick polyethylene (PE) separation membrane between them, and filling the device with electrolyte. The electrolyte was prepared by dissolving 1.0 M LiPF6 in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate (EC / EMC mixed volume ratio of 3 / 7).

[0085] Example 3: Manufacturing of a lithium secondary battery Carbon nanotubes were used as the conductive material, and polyvinylidene fluoride (PVDF) was used as the binder. A cathode active material slurry was prepared by mixing 97 parts by weight of the surface-modified cathode active material from Example 1-2, 1.5 parts by weight of the conductive material, and 1.5 parts by weight of the binder. The prepared slurry was coated onto an aluminum current collector and dried to prepare the cathode. At this time, the particle size distribution of the oxide-based solid electrolyte (LATP) was D10: 0.237 μm, D50: 0.347 μm, D90: 0.497 μm, and span: 0.749. Graphite was used as the anode active material, and without using an oxide-based solid electrolyte, the anode was prepared by mixing the anode active material, conductive material, and binder in a weight ratio of 96.5:1.5:2, and then performing the same process as for the cathode.

[0086] A lithium secondary battery in bicell form was manufactured by placing the prepared positive and negative electrodes facing each other, placing a 15 μm thick polyethylene (PE) separation membrane between them, and filling the device with electrolyte. The electrolyte was prepared by dissolving 1.0 M LiPF6 in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate (EC / EMC mixed volume ratio of 3 / 7).

[0087] Comparative Example 1: Positive Electrode Active Material A lithium nickel-cobalt-manganese composite oxide (NCM603; D50: 5μm) containing 65 mol% nickel relative to the total transition metal was used.

[0088] Comparative Example 2: Manufacturing of Lithium-ion Secondary Batteries A positive electrode active material slurry was prepared by mixing 97 parts by weight of the positive electrode active material from Comparative Example 1, 1.5 parts by weight of conductive material, and 1.5 parts by weight of PVDF. The prepared slurry was coated onto an aluminum current collector and dried to prepare the positive electrode. The same conductive material, binder, negative electrode, and electrolyte as in Example 2 were used.

[0089] A lithium secondary battery in a bicell configuration was manufactured by placing the prepared positive and negative electrodes facing each other, placing a 20 μm thick polyethylene (PE) separation membrane between them, and filling the area with an electrolyte.

[0090] Comparative Example 3: Sample without preliminary dispersion A cathode active material slurry was prepared by mixing 96 parts by weight of the cathode active material from Comparative Example 1, 1.5 parts by weight of conductive material, 1.5 parts by weight of PVDF, and 1 part by weight of oxide-based solid electrolyte (LATP). The prepared slurry was coated onto an aluminum current collector and dried to prepare the cathode. The conductive material, binder, anode, and electrolyte were the same as those used in Example 2. The particle size distribution of the oxide-based solid electrolyte (LATP) was D10: 0.302 μm, D50: 0.512 μm, D90: 3.3 μm, and span: 5.766.

[0091] A lithium secondary battery in a bicell configuration was manufactured by placing the prepared positive and negative electrodes facing each other, placing a 20 μm thick polyethylene (PE) separation membrane between them, and filling the area with an electrolyte.

[0092] Experimental example 1) Figure 2 shows SEM images of the surface-modified cathode active materials in Comparative Example 1 and Example 1, and mapping images of the Ti element of the oxide-based solid electrolyte obtained from EDS analysis of the active material surface, respectively.

[0093] As a result, compared to a cathode active material that has not undergone surface modification, the surface-modified cathode active material according to the embodiment of the present invention shows a uniform dispersion of oxide-based solid electrolyte nanoparticles, and it can be confirmed that a uniform solid electrolyte coating layer is formed on the surface of the cathode active material after heat treatment.

[0094] 2) Furthermore, the electrochemical properties of the lithium secondary batteries of Example 2, Example 3, and Comparative Examples 2 and 3 were evaluated. Specifically, for each sample, the capacity change and charge / discharge change were measured while repeating the charge / discharge test three times at room temperature (approximately 25°C) under the conditions of 1) 0.2C-0.33C charging (cut off: 4.2V, 0.05C) and 2) 0.2C-0.33C discharge (cut off: 2.5V), and the results are shown in Figure 3.

[0095] As a result, in Examples 2 and 3, where surface-modified cathode active material was applied, it was confirmed that the solvent removal rate of the electrolyte was accelerated, the ionic conductivity at low temperatures was increased, and the cell resistance and output characteristics were improved.

[0096] 3) For the lithium secondary batteries of Examples 2 and 3, and Comparative Examples 2 and 3, the resistance was measured for each state of charge (SOC) while repeatedly performing charge-discharge tests at room temperature (approximately 25°C) under the conditions of 1) 0.2C-0.33C charging (cut-off: 4.2V, 0.05C) and 2) 0.2C-0.33C discharging (cut-off: 2.5V). Specifically, the charge-discharge tests were repeatedly performed under SOC settings of 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, and 10%, and the DC resistance (2.5C discharge (cut-off: 10s or 2V)) was measured after each charge-discharge. The results of these resistance measurements for each charge state are shown in Figure 4 and also in Table 1 below.

[0097] [Table 1]

[0098] As a result, in Example 2, where a surface-modified cathode active material was applied, it was confirmed that the solvent removal rate of the electrolyte was accelerated, the ionic conductivity at low temperatures was increased, and the cell resistance and output characteristics were improved.

Claims

1. A step of producing a solid electrolyte dispersion containing an oxide-based solid electrolyte and a solvent, The steps include coating the surface of the electrode active material with the solid electrolyte dispersion, The steps include: heat-treating the coated electrode active material to form a surface-modified electrode active material; A method for producing a surface-modified electrode active material, including the active material itself.

2. The method for producing a surface-modified electrode active material according to claim 1, wherein the step of producing the solid electrolyte dispersion includes mixing 5 to 70 parts by weight of the oxide-based solid electrolyte and 30 to 95 parts by weight of the solvent.

3. The method for producing a surface-modified electrode active material according to claim 1, wherein in the step of producing the solid electrolyte dispersion, the oxide-based solid electrolyte is dispersed in the solvent using a bead-milling method.

4. The method for producing a surface-modified electrode active material according to claim 1, wherein the oxide-based solid electrolyte comprises one or more lithium metal oxides or lithium metal phosphor oxides selected from Nasicon-type solid electrolytes, Lisicon-type solid electrolytes, Garnet-type solid electrolytes, Perovskite-type solid electrolytes, and LiPON-type solid electrolytes.

5. The method for producing a surface-modified electrode active material according to claim 1, wherein the oxide-based solid electrolyte comprises one or more compounds selected from the group consisting of LAGP (lithium aluminum germanium phosphate) compounds, LLZO (lithium lanthanum zirconium oxide) compounds, LATP (lithium aluminum titanium phosphate) compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) compounds, LLTO (lithium lanthanum titanium oxide) compounds, LSTP (lithium silicon titanium phosphate) compounds, and LGPO (lithium germanium phosphate) compounds.

6. The method for producing a surface-modified electrode active material according to claim 1, wherein the oxide-based solid electrolyte has a particle size distribution of one or more from 100 nm to 1 μm for D50 and 400 nm to 1.5 μm for D90.

7. The method for producing a surface-modified electrode active material according to claim 6, wherein the oxide-based solid electrolyte in the solid electrolyte dispersion has a particle size distribution of D50 300 to 700 nm, D90 400 to 900 nm, and span (span) 1 or less.

8. The method for producing a surface-modified electrode active material according to claim 1, wherein the step of coating the solid electrolyte dispersion is performed by a spray coating method.

9. The method for producing a surface-modified electrode active material according to claim 1, wherein the oxide-based solid electrolyte is contained in an amount of 0.3 to 5 parts by weight per 100 parts by weight of the electrode active material.

10. The method for producing a surface-modified electrode active material according to claim 1, wherein the heat treatment step includes heat treatment at a temperature equal to or greater than the glass transition temperature (Tg) of the oxide-based solid electrolyte.

11. The method for producing a surface-modified electrode active material according to claim 1, wherein in the heat treatment step, the surface-modified electrode active material is formed by firing at a temperature of 600 to 1000°C for 1 to 3 hours.

12. Metal current collectors; and An active material layer formed on the metal current collector, comprising a surface-modified electrode active material manufactured by the manufacturing method described in any one of claims 1 to 11; Electrodes for lithium secondary batteries, including those mentioned above.

13. A positive electrode; a negative electrode; and an electrolyte comprising a lithium salt and a non-aqueous organic solvent; A lithium secondary battery comprising the electrode for lithium secondary battery described in claim 12 as the positive electrode.